On Seamus Heaney, R. F. Foster (2020). Issue 1 (1st April 2022) - Butler, Jim
Review of: On Seamus Heaney, R. F. Foster (2020)Princeton, NJ and Oxford: Princeton University Press, 248pp., ISBN 978-0-69121-147-3 h/bk, £14.99